IMPLEMENTASI SAMBHAṢAṆA DALAM UPAYA MENGEMBANGKAN KEMAMPUAN DASAR BERBAHASA SANSKERTA - IDA KADE SUPARTA (Universitas Mahasaraswati K. Mataram, 2022)
The view of sanskrit as a dead language and a language that is difficult to learn is not completely correct and must slowly be eliminated. Awareness to increase the existence of sanskrit has been initiated in several parts of the world by making it a daily communication language. The basic learning of sanskrit which is initiated at this time places more emphasis on communication skills, not on the grammatical structure. Learning is packaged more effectively and efficiently through the sambhaṣaṇa (conversation) method by applying simple grammar or communication patterns. Conversation is a very common method in learning other languages, but it has become a new design in teaching sanskrit. Thus, this study was conducted to analyze and develop the concept of implementing the sambhaṣaṇa method in relation to developing basic sanskrit language skills. This research was conducted through a qualitative approach by presenting the data descriptively. The results showed that the application of the sambhaṣaṇa (conversation) method was very effective and efficient in developing basic sanskrit language skills. Learning sanskrit through the sambhaṣaṇa method begins with the introduction of objects and activities in the surrounding environment. Sanskrit conversation material can be arranged in the form of special themes that are relevant to the daily lives of students. During the learning process, the teacher has the task of correcting errors that arise from conversations practiced by students. The success of the learning is determined by the motivation of the students, the competence of the teacher, the intensity of the exercise, and the vocabulary mastered by the students.